Effect of acupuncture at Back-Shu points on gut microbiota in insomnia model rats based on metagenomic sequencing technology - Qi, Shangwen; Qian, Jiahui; Li, Yubing; Li, Yujie; Li, Wei; Gao, Xiyan (Frontiers in Microbiology, 2025)
BackgroundIncreasing evidence indicates a bidirectional interaction between the gut microbiota and sleep regulation via the microbiota–gut–brain axis. Acupuncture is widely used to treat insomnia, and its efficacy may be mediated in part by modulation of the gut microbiota and its metabolic pathways.MethodsA rat model of insomnia was established by intraperitoneal injection of para-chlorophenylalanine (PCPA). Rats received acupuncture at Back-Shu points for 2 weeks. Sleep behavior was assessed using the pentobarbital-induced sleep test, and fecal samples were collected for metagenomic sequencing to analyze changes in gut microbial composition and function before and after acupuncture.ResultsCompared with the model group, acupuncture significantly shortened sleep latency and prolonged sleep duration. Metagenomic analysis revealed that acupuncture partially restored the PCPA-induced decline in α-diversity and markedly altered β-diversity. Functionally, acupuncture enriched beneficial taxa such as Lactobacillus johnsonii and Ligilactobacillus murinus, and promoted pathways involved in tryptophan and glutamate metabolism as well as short-chain fatty acid (SCFA) synthesis. These changes may act by restoring neurotransmitter balance, strengthening gut barrier integrity, and modulating immune responses. Notably, SCFAs can activate G-protein–coupled receptors to suppress overactivation of the hypothalamic–pituitary–adrenal (HPA) axis, counteracting insomnia-related pathophysiology.ConclusionAcupuncture at Back-Shu points ameliorates PCPA-induced insomnia-like behavior in rats and beneficially remodels gut microbiota structure and metabolic function. These findings support a key role for the microbiota–gut–brain axis in acupuncture’s regulation of sleep and provide a theoretical basis for developing microbiota-targeted adjunctive therapies for insomnia.